ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN CAFE MENGGUNAKAN ANALISIS DISKRIMINAN - Bravendi, Diantina; Dwidayati, Nur Karomah; Sunarmi, Sunarmi (Universitas Muhammadiyah Semarang, 2017)
Cafe is one of a kind restaurant that usually serve snacks and baverages. The exsistance of cafe arround Universitas Negeri Semarang campus is gettingmore, one of them is Soda Ocean Cafe. Hence, the cofe owner must give the bestservice and facility for the consumer. This study aims to determine what factorsare the satisfaction of Cafe customers, as well as seeking discriminant functionand the accuracy of the function. Consumer satisfication with servicse andfacilities can be found out by discriminant analysis. Independent ariables in thisanalysis are sound system, live performance, environment, security, service,price, the variety of foods and drinks, cosiness, and location and dependentvariable is consumer satisfication. Analysis results shows that there is asignificant difference betweenthe type of satisfied consumer and dissatisfiedconsumer. The satisfaction factors of Soda Ocean Cafe customer areenvironment, security, and live performance. Discriminant function in thisanalysis isD=-3,269+0,783 nuansa - 0,121Keamanan + 0,646 HiburanThat function has 71,6% classification accuracy. Hence, the discriminantfunction can be used ti predict the type of consumers. Keywords: Cafe, Kepuasan Pelanggan, Analisis Diskriminan.